Assessing student’s job preferences with a choice based model approach - Kokaveshi, Ergita; Gjoka, Eri (Edelweiss Applied Science and Technology, 2025)
In this article, the Choice-Based Models approach was utilized to assess the job preferences of students at the Faculty of Economics in Tirana, Albania. In many fields where choice prediction is important, it is crucial to comprehend how changes in the attributes of alternatives impact preferences for them. To that end, part-worth utilities for each attribute level were estimated. The results of our analysis highlighted how crucial it is to consider more than just financial figures when assessing compensation packages. While starting pay is important, long-term career prospects are highly valued, and students prefer higher compensation growth rates over time. Salary and growth rates together show that students consider factors other than immediate financial gain. Career decisions seem to be motivated by the need for both financial security and the possibility of gradual advancement. This implies that students might prefer companies and positions that offer a clear and achievable path for career advancement over those that offer high starting pay with uncertain long-term outcomes.